Thermal Debinding of Metal Injection Molded Parts with an Agar-Gel Binder System - Li, Xiaoyun (My University, 2007)
Metal injection molding (MIM) employs the advantages of injection molding and powder metallurgy and provides a high productivity means to form intricate, low-cost, high performance metal parts. One of the most unique characteristics of MIM is the binder system and the consequent debinding step, which is considered to be major process improvement barrier in the MIM process. A MIM part with a thick section suffers from a long debinding cycle and it is difficult to avoid defects. Therefore, it is always of interest to find out a method to quickly debind a thick part without defects. PowderFlo® feedstock combines metal powder with an aqueous agar-gel binder system and requires simple air-drying followed by thermal debinding. However, previous studies on this agar-gel binder feedstock mainly focus on sintering, while the debinding step has lacked sufficient attention. A debinding study on agar-gel binder system is conducted in the present project. The metal compacts are formed via compression molding and injection molding, followed with thermal debinding in order to understand the effects of process parameters on debinding with respect to thickness to determine a good debinding schedule. The thickness transition between thick and thin section is particularly important in the debinding to find a protocol to make parts with both thick and thin sections. Thermal debinding experiments show that the initial heating rate is the most significant factor due to it may cause visible defect directly and an increase of initial and secondary heating rates may retard binder removal. The air-drying time has less influence on binder extraction for thicker section. Extending the holding time for water and polymer removal is beneficial to obtain better dimensional control. The overall debinding process parameters have larger effects on thicker parts. For the thickness transition, it is suggested to avoid the combination of too thin and too thick section, increase the joint area, and provide uniform packing during molding.
This thesis is missing page 48, all other copies of this thesis are missing the page as well. -Digitization Centre
Keywords: thermal debinding; metal injection